Magical Realism Analysis of the Character Nora Seed in the Midnight Library - Pakpahan, Ashira Netania Aprina; Tamba, Mariana Cecilia; Sumbayak, Elizabeth Yoshelita; Putri, Vera Aprilia; Nehe, Kristenika Adel Kurnia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the representation and function of magical realism in Matt Haig’s The Midnight Library (2020) through analysis of the character Nora Seed. Magical realism, as a literary mode that seamlessly blends realistic narration with extraordinary elements, provides a productive framework for exploring Nora’s psychological transformation and existential struggle. While previous studies on The Midnight Library have largely emphasized psychological, sociological, and philosophical perspectives, such as suicide, trauma, and existentialism, limited attention has been given to the role of magical realism as a narrative strategy that shapes the protagonist’s development. Employing a qualitative descriptive method, this research conducts close textual and thematic analysis of the novel to identify key characteristics of magical realism and examine how they influence Nora’s journey from despair to self-acceptance. The findings reveal that the Midnight Library functions not merely as a fantastical setting but as a magical realist space that externalizes Nora’s internal conflicts, regrets, and alternative identities. The matter-of-fact narration of the metaphysical library, the coexistence of life and death, and the merging of realistic and fantastical realms enable the narrative to portray psychological healing in a concrete and accessible form. Through magical realism, Nora is able to confront multiple versions of herself and ultimately reconstruct her understanding of meaning, choice, and existence. This study concludes that magical realism in The Midnight Library operates as a central literary mechanism rather than a decorative element, demonstrating the genre’s evolving role in contemporary literature as a means of representing mental struggle, self-reflection, and existential recovery.